2017
DOI: 10.1039/c6cp08066a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of g-C3N4-based type II and Z-scheme heterojunction anodes with improved charge separation for photoelectrojunction water oxidation

Abstract: Graphitic carbon nitride (g-CN) has been widely studied as a metal-free photocatalyst, leading to some excellent results; however, the rapid recombination of photogenerated charge carriers substantially limits its performance. Here, we establish two types of g-CN-based heterojunction (type II and nonmediator assisted Z-scheme) photoanodes on a transparent conducting substrate via coupling with rod-like and nanoparticulate WO, respectively. In these composites, g-CN film grown by electrophoretic deposition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…To further understand the effect of the CoPy layer in the assembled photoanodes on interface modulation, IMPS measurements developed by Peter and co‐workers were carried out. IMPS was conducted on different photoanodes to compare the relative rates of charge recombination ( k rc ) and transfer ( k ct ) occurring at the S–E interface (Figure a) . Pure BV showed a ringlike curve (Figure b), meaning k ct ≪ k rc , that is, surface recombination plays a substantial role, namely, the bulk BV exhibits poor PEC performance, which is consistent with a previous report .…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…To further understand the effect of the CoPy layer in the assembled photoanodes on interface modulation, IMPS measurements developed by Peter and co‐workers were carried out. IMPS was conducted on different photoanodes to compare the relative rates of charge recombination ( k rc ) and transfer ( k ct ) occurring at the S–E interface (Figure a) . Pure BV showed a ringlike curve (Figure b), meaning k ct ≪ k rc , that is, surface recombination plays a substantial role, namely, the bulk BV exhibits poor PEC performance, which is consistent with a previous report .…”
Section: Figuresupporting
confidence: 86%
“…According to the our previous work, the transit time ( τ d ) values of different samples can be estimated from τ d =(2π f max ) −1 , in which f max is the characteristic frequency at the lowest point of the IMPS plot and shows an increasing trend: R‐BV/CoPy/FN‐H<BV/CoPy/FN‐H< BV/FN‐H<BV/CoPy<BV (Figure d; see also Table S5). Typically, the calculated τ d values for BV/CoPy/FN‐H and BV/FN‐H are 0.92 and 1.00 ms, respectively, which indicates that the BV/CoPy/FN‐H photoanodes show a higher charge‐transfer rate than that of BV/FN‐H because the “setter” (e.g., CoPy) accelerates the hole transfer from BV to the OEC surface.…”
Section: Figurementioning
confidence: 99%
“…Thus the PEC performance of the composite photoanode with Z‐scheme heterojunction is improved. Similar work has also been done by Liu's team . Based on ultraviolet photoelectron spectroscopy (UPS) spectra and UV–vis absorption spectra, they investigated the band structure of WO 3 and g‐C 3 N 4 and found that both the CB and VB of g‐C 3 N 4 are more negative than those of WO 3 .…”
Section: Heterojunction Constructionmentioning
confidence: 68%
“…According to the our previous work, [37] the transit time (t d )v alues of different samples can be estimated from t d = (2pf max ) À1 ,i nw hich f max is the characteristic frequencya tt he lowest point of the IMPS plot and shows an increasing trend: R-BV/CoPy/FN-H < BV/CoPy/FN-H < BV/FN-H < BV/ CoPy < BV (Figure 3d;s ee also Table S5). Ty pically,t he calculated t d values for BV/CoPy/FN-H and BV/FN-H are 0.92 and 1.00 ms,r espectively,w hich indicates that the BV/ CoPy/FN-H photoanodes show ah igher charge-transfer rate than that of BV/FN-H because the "setter" (e.g., CoPy) accelerates the hole transfer from BV to the OEC surface.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…IMPS was conducted on different photoanodes to compare the relative rates of charge recombination (k rc )a nd transfer (k ct )o ccurring at the S-E interface (Figure 3a). [36,37] Pure BV showed ar inglike curve (Figure 3b), meaning k ct ! k rc ,t hat is,s urface recombination plays as ubstantial role, namely,the bulk BV exhibits poor PEC performance,which is consistent with ap revious report.…”
mentioning
confidence: 99%